Pengaruh Computer Fear dan Computer Anticipation terhadap Keahlian Siswa Akuntansi dalam Menggunakan Aplikasi MYOB - Elen Yuri Astia; Diyah Probowulan; Nina M Nina M (BUDGETING : Journal of Business, Management and Accounting, 2019)
The purpose of this study was to determine the effect of computer fear and computer anticipation on students' ability to use the MYOB application. This research uses a quantitative approach with a comparative causal method. The study was conducted on students in grades 1 and 2 of Al-Hasan Panti Vocational School, Panti District, Jember Regency. The results of the study, computer fear with the expertise of accounting students in using the MYOB application, that the value of t-count is smaller than t-table (-2.457 <1.993) with a significance level of 0.016, the effect of computer anticipation on the expertise of accounting students in using the MYOB application, namely t -calculates greater than t-table and the significance level is less than 0.05. Conclusion, there is no influence of computer fear with the expertise of accounting students in using the MYOB application, then there is the influence of computer anticipation on the expertise of accounting students in using the MYOB application Keywords: Computer Fear, Computer Anticipation, Student Skills